Analgesic activity test of Inggu leaf (Ruta angustifolia [L.] Pers) with Tail Flick and Writhing Test method - Ariasti, Mia; Busyairi Muhsin, Lalu (Journal of Natural Sciences and Mathematics Research, 2024)
Pain is a sensory and emotional experience related to tissue damage. This study aims to determine the analgesic effect of ethanol extract from Inggu leaves and the effective dose of ethanol extract of Inggu leaves by tail flick and writhing test methods. The tail flick and writhing test methods have been widely used to develop non-steroidal anti-inflammatory drugs. Steroid and flavonoid compounds contained in Inggu leaves are thought to have an effect as analgesics. The powder of Inggu leaves was extracted using the maceration method with 96% ethanol solvent. A total of 25 Wistar male white rats were divided into 5 groups, namely positive control mefenamic acid 9 mg/200 g BB, negative control CMC Na 1%, ethanol extract of Inggu leaves doses of 5 mg/200 g BB, 10 mg/200 g BB and 20 mg/200 g BB. The data obtained were analyzed using the ANOVA test, and then the LSD test was used to determine the differences between groups. The results showed that the 5 mg/200 g BW extract doses, 10 mg/200 g BW, 20 mg/200 g BW, and positive control significantly differed from the negative control group. The extract dose of 20 mg/200 g BB is comparable to the positive control, indicating that the extract dose of 20 mg/200 g BB has the most effective analgesic activity.